If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(3) + 3 = 0 Reorder the terms for easier multiplication: 3F + 3 = 0 Reorder the terms: 3 + 3F = 0 Solving 3 + 3F = 0 Solving for variable 'F'. Move all terms containing F to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 3F = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 3F = 0 + -3 3F = 0 + -3 Combine like terms: 0 + -3 = -3 3F = -3 Divide each side by '3'. F = -1 Simplifying F = -1
| 5(3x+4)=0 | | 34=3x+10 | | 5w+7-2(-7w-4)=3(w-1) | | 5(3x-4)=0 | | 4a^2+10a-22=0 | | 14c-6c= | | -11+6+7n-9n=n+1 | | 4x-2(5x-8)=-56 | | (6x)=6(xy) | | 2m^2-7m-7m-13=-10 | | 5w-5+2(3w+7)=-5(w+1) | | 15u-8u=49 | | 6=4x/(12-x) | | X-2(-.3)=2 | | 13=5x+11 | | 3n+2=3 | | 3(2+2y)+4y=3 | | 7+4q=11+34 | | 6+6x=6(x-5) | | 7(x+4)=-2(5x-5)+2x | | (2x+1)-(-4x-9)= | | x+3x+6x=3450 | | 12(10)+3(14)=162 | | 9-x=x+12 | | 7-2n=4 | | 8(10)+3(14)=122 | | 4z-5=8x+3 | | -3(-2w+3)-9w=3(w-7)-3 | | 2y(y)=400 | | 2.1x-12.2= | | 481.194=13.4*6.3*w | | 3x-4+2x+10=21 |